Svätý Blažej ako „vlčí pastier“ v textovej tradícii z českého, slovenského a maďarského prostrediaSaint Blaise as a “Wolf Shepherd” in a Text Tradition from Czech, Slovak and Hungarian Surroundings - Golema, Martin (Studia mythologica Slavica, 2008)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The author of the study, working with less known texts from Czech, Slovak and Hungarian surroundings, tries to confirm conclusions about a mythological couple of <span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">“wolf shepherds<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">” (its origin goes back to the early Slavonic text horizon) published up to the present, but he also shows some other ways of reconstructing of the old myth linked with this mythological couple. St. Blaise was evidently established in the place under research as a common interpretatio christiana of demonic and magic related member of this couple – the Slavonic god Veles.